Estudo da atividade das enzimas envolvidas na ossificação de frangos de corte normais e acometidos por discondroplasia tibial - Santos, Luiz Flávio José dos [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The tibial dyschondroplasia is attributed to an asynchrony in the endochondral ossification process, leading to an accumulation of non-calcified and non-vascularized cartilage in the place where the trabecular bone should be formed. A synchronized action of ectoenzyme nucleotide phosphodiesterase pyrophosphatase (PC-1), alkaline phosphatase and acid phosphatase is required in the biological calcification process, because they act in the regulation of pyrophosphate concentrations, which in high concentrations is an inhibitor of calcification and may lead to the development of tibial dyschondroplasia. The birds were divided into normal and dyschondroplasic, sacrificed, then the tibiae were removed, frozen in liquid nitrogen and stored at -70 °C. Afterwards, the growth plates were homogenized, submitted to different treatments to make each enzyme extract and then were aliquoted, frozen and stored at -70 °C for posterior enzyme assays and protein dosage. There was no difference between the specific activity of PC-1 extracted from normal birds compared to that obtained from dyschondroplasic birds, on the other hand the specific activity of alkaline phosphatase was lower in birds with tibial dyschondroplasia, when compared with healthy birds, suggesting that dyschondroplasia may be attributed to an increase in the concentration of pyrophosphate, which may cause prejudice to mineralization by binding directly to the hydroxyapatite crystals and preventing their growth and also because there is no production of inorganic phosphate. The acid phosphatase activity decreased in dyschondroplasic birds when compared to the normal ones, suggesting that the growth plate has its remodeling functions affected. Our results suggest that the tibial dyschondroplasia can be attributed to the decrease in alkaline phosphatase activity, which leads to an increase in inorganic pyrophosphate concentration, inhibiting...
Keywords: Ossificação; Fosfatase alcalina; Enzimas; Produção animal; Proteinas - Analise; Enzymes